Answer:
0.965925826
0.258819045
Step-by-step explanation:
→If you were to calculate [tex]sin(75)[/tex], you would have a total of:
0.965925826
→If you were to calculate [tex]cos(-75)[/tex], you would have a total of:
0.258819045
Describe and correct the error in finding csc θ, given that θ is an acute angle of a right triangle and cos θ =7/11
Answer:
cosecθ = 1/sinθ = 11/6√2Step-by-step explanation:
Given that cos θ =7/11, cosec θ = 1/sinθ in trigonometry.
Based on SOH, CAH, TOA;
cosθ = adjacent/hypotenuse = 7/11
adjacent = 7 and hyp = 11
Since sinθ = opp/hyp, we need to get the opposite to be able to calculate sinθ.
Using pythagoras theorem to get the opposite;
[tex]hyp^{2} = adj^{2} + opp ^{2} \\opp = \sqrt{hyp^{2} - adj^{2} } \\opp = \sqrt{11^{2} - 7^{2}} \\opp = \sqrt{72} \\opp = 6\sqrt{2}[/tex]
sinθ = 6√2/11
cosecθ = 1/sinθ = 1/( 6√2/11)
cosecθ = 1/sinθ = 11/6√2
Note the error; cscθ[tex]\neq[/tex] 1/cosθ but cscθ = 1/sinθ
what is the absolute value of -2/2
-2/2 = -1/1 = -1
Therefore, the absolute value of -2/2 is -1.
Multiple Representations:Question 1
Given the equation below, if x = 12, what is the value of y?
y= x + 15.1
Answer:
y = 27.1
Step-by-step explanation:
We have the value of x:
x = 12
and we need to find the value of y in the expression:
y = x + 15.1
as we can see by the equation, the value of y depends on the value of x.
thus, we substitute x = 12 on the previous equation:
y = 12 + 15.1
y = 27.1
the value of y is 27.1
open the word document
Answer:
Total mean: 4.3
Step-by-step explanation:
(mean for home goals)
Mean: 2.5
(mean for away goals)
Mean: 1.8
it tells us to find the total games played all together..
so:
2.5 + 1.8 = 4.3
What is the solution to the equation shown below? یہ اس x + 5 = 1 A x=-6 B x=4 C x= -4.5 D x=9
Answer:
x = -4None of the answers is correctStep-by-step explanation:
Given the equation x + 5 = 1, to get the solution to the equation, we need to find the value of x
Step 1: Subtract 5 from both sides of the equation
x+5-5 = 1-5
x = 1-5
Step 2: Find the value of the unknown variable x
x = -4
The solution to the equation is x = -4
Line A's equation is y = 6x - 5. Line B is parallel to Line A and and goes through the
point (3, 10). Write the equation for Line B in slope-intercept form.
Answer:
y = 6x - 8
Step-by-step explanation:
line a: y = 6x- 5
10 = 6(3) - b
10 = 18 - b
10 - 18 = -b
-8 = -b
8 = b
Factor completely x2 + 16.
Answer:
2(x+8)
Step-by-step explanation:
2x+16
2(x+8)
Answer:
unfactorable with real numbers
in the complex realm
(x-4i) (x+4i)
Step-by-step explanation:
x^2+16
We can only factor this with imaginary numbers
(x^2 - (-4i)^2)
This is the difference of squares
(x -4i) (x+4i)
A pair of shoes is originally priced at $120.00 It is on sale for 35% off. Find the total percent that you would pay: *
Answer:
$43.75 (65%)
Step-by-step explanation:
35% of 125= 43.75
.35 times 125+ 43.75
Answer:
78$
Step-by-step explanation:
First we need to know the percent of the birr. 120×35÷100= 42$then we minus the percent of birr from the total amount 120$-42%then we need to pay 78$Need help!!! Now!!!
Answer:
50
Step-by-step explanation:
c = cell phone cost
t = 5c
computer = 2.5 t = 2.5 ( 5c) =12.5 c
The total = 925
c+t+ computer = 925
c + 5c+ 12.5c = 925
Combine like terms
18.5 c = 925
Divide each side by 18.5
18.5c /18.5 = 925/18.5
c = 50
Answer:
Step-by-step explanation:
From the end of the problem to the beginning of the problem (this is often how you need to "decipher" story problems...go at it backwards!), we see that the cost of everything Tony bought is, in the end, based on the cost of the cell phone. The TV is 5 times as much as the cell phone, and the computer is 2.5 times as much as the TV...which is based on the cell phone. So the cell phone is our "main" unknown. We'll call that x.
If the TV is 5 times the cell phone, then the
TV = 5x
If the computer is 2.5 times the TV, then the
computer = 2.5(5x) = 12.5x
The cost of all these added together is 925. Therefore,
x + 5x + 12.5x = 925 and
18.5x = 925 so
x = 50
The cell phone cost $50. Choice G.
Can someone help me plz :)
Answer:
4
4
4
4
Step-by-step explanation:
Simplify (x+3)^2 - 6x
Answer:
[tex] {x}^{2} + 9[/tex]
Step-by-step explanation:
[tex] {(x + 3)}^{2} - 6x \\ \\ = {x}^{2} + {3}^{2} + 2 \times x \times 3 - 6x \\ \\ = {x}^{2} + 9 + 6x - 6x \\ \\ = {x}^{2} + 9[/tex]
Answer:
The answer is x² + 9.
Step-by-step explanation:
First, you have to get rid of bracket of square :
[tex] {(a + b)}^{2} \: ⇒ \: {a}^{2} + 2ab + {b}^{2} [/tex]
[tex] {(x + 3)}^{2} [/tex]
[tex] = (x + 3)(x + 3)[/tex]
[tex] = {x}^{2} + 6x + 9[/tex]
Next, you can simplify :
[tex] {x}^{2} + 6x + 9 - 6x[/tex]
[tex] = {x}^{2} + 9[/tex]
What is the next term of the geometric sequence? 27/16, -9/4 3
Answer:
-4
Step-by-step explanation:
khan academy
Solving 2+2x=3+2x can provide justification that the equation does not have a solution. Investigate this equation using a graph and inverse operations.
Step-by-step explanation:
The main goal is to separate the values on opposite sides of the equal sign.
2 + 2x = 3 + 2x
-2 -2 ⬅Subtract 2 from both expressions
2x = 1 + 2x
-2x - 2x ⬅Subtract 2x from both sides.
0 = 1
Answer:
0 does not equal 1, which means that this equation is inconsistent. In other words, there is no solution. 0 does not equal 1, so 2 + 2x does not equal 3 + 2x.
I hope this helps! :)
solve it
7x−3(x−6)=2
Answer:
x=-4
Step-by-step explanation:
Answer:
x = -4
Step-by-step explanation:
7x−3(x−6)=2
Distribute
7x -3x + 18 = 2
4x +18 =2
Subtract 18 from each side
4x +18-18 = 2-18
4x = -16
Divide by 4
4x/4 = -16/4
x = -4
if Y is directly proportional to x and y = 10 when x = 2, find
I) an equation connecting x and y
ii) the value of y when x = 10
III) the value of x when y = 60
p.s please give me a answer quickly
Answer:
I) Y=5x
II) Y=50
III)X=12
Step-by-step explanation :
I) Y=5x
II) Y=5(10)
Y=50 when x=10
III)Y=5x
60=5x
X=60/5
X=12 when y=60
Hope this helps..
A bag holds 20 jelly beans: 5 red, 10 green, 4 blue, and 1 black. What is the probability of choosing two consecutive blue jelly beans without replacement
Answer:
10/20 for green, then 4/19 for blue. 10/20 * 4/19 = 2/19
Step-by-step explanation:
Explanation is above. If you need any more help let me know.
I will give you 10B points plus mark someone again for the Brainliest if you get this right. a:15 b:7 c:4
For this expression,a=15,b=7 and c=4
Hope it helpsGood luck on your assignment
For each system of equations, drag the true statement about its solution set to the box under the system. HURRY PLEASE!
Answer:
Ok, some theory first:
If we have more variables than linear independent equations, then we have infinite solutions.
If we have the same number of linearly independent equations and variables, we can have a unique solution or no solution.
we have no solution in cases where:
y = x + 3
y = x - 3
this leads to:
x + 3 = x - 3
+3 = -3
so this system has no solutions.
The first system of equations is:
y = x + 5
y = 2x + 5
Now, you can see that we have 2 variables, and 2 linear independent equations, this means that we have only one solution for this system
So here we have "One solution, the graph of these lines should intersect at one point" and the point is (0, 5)
The second system is:
y = x + 5 + x = 2x + 5
y = 2x+ 5
Both equations are the same, so here we have 2 variables and only one equation, this means that we have infinite solutions for this system.
here the correct option is the one that says "infinitely many solutions, both right side and left side are equivalent expressions"
Answer:
For y = x+5
y=2x+5 It is one solution
For y = X+5+X and Y = 2X + 5 Infinitely Many Solutions both the right and left sides of the equations are equivalent expressions. See photo below
Step-by-step explanation:
What is 12 radical 2 divided by 2 radical 6 in simplest form
Answer:
[tex]=2\sqrt{3}\\\mathrm{Decimal:\quad }\:3.46410[/tex]
Step-by-step explanation:
[tex]\frac{12\sqrt{2}}{2\sqrt{6}}\\\mathrm{Divide\:the\:numbers:}\:\frac{12}{2}=6\\=\frac{6\sqrt{2}}{\sqrt{6}}\\\mathrm{Apply\:radical\:rule}:\quad \sqrt[n]{a}=a^{\frac{1}{n}}\\\sqrt{6}=6^{\frac{1}{2}}\\=\frac{6\sqrt{2}}{6^{\frac{1}{2}}}\\\mathrm{Apply\:exponent\:rule}:\quad \frac{x^a}{x^b}=x^{a-b}\\\frac{6^1}{6^{\frac{1}{2}}}=6^{1-\frac{1}{2}}\\=\sqrt{2}\cdot \:6^{-\frac{1}{2}+1}\\\mathrm{Subtract\:the\:numbers:}\:1-\frac{1}{2}=\frac{1}{2}\\=6^{\frac{1}{2}}\sqrt{2}[/tex]
[tex]\mathrm{Apply\:radical\:rule}:\quad \:a^{\frac{1}{n}}=\sqrt[n]{a}\\6^{\frac{1}{2}}=\sqrt{6}\\=\sqrt{6}\sqrt{2}\\\mathrm{Factor\:integer\:}6=2\cdot \:3\\=\sqrt{2\cdot \:3}\sqrt{2}\\\mathrm{Apply\:radical\:rule}:\quad \sqrt[n]{ab}=\sqrt[n]{a}\sqrt[n]{b}\\\sqrt{2\cdot \:3}=\sqrt{2}\sqrt{3}\\=\sqrt{2}\sqrt{3}\sqrt{2}\\\mathrm{Apply\:radical\:rule}:\quad \sqrt{a}\sqrt{a}=a\\\sqrt{2}\sqrt{2}=2\\=2\sqrt{3}[/tex]
Answer:
[tex]2 \sqrt{3} [/tex]Step-by-step explanation:
[tex] \frac{ 12\sqrt{2} }{2 \sqrt{6} } [/tex]
Reduce the fraction with 2
[tex] = \frac{6 \sqrt{2} }{ \sqrt{6} } [/tex]
Simplify the expression
[tex] \frac{6}{ \sqrt{3} } [/tex]
Multiply the fraction by [tex] \frac{ \sqrt{3} }{ \sqrt{3} } [/tex]
[tex] \frac{6}{ \sqrt{3} } \times \frac{ \sqrt{3} }{ \sqrt{3} } [/tex]
To multiply the fractions, multiply the numerators and denominators separately
[tex] \frac{6 \sqrt{3} }{ \sqrt{3 \times \sqrt{3} } } [/tex]
When a square root of an expression is multiplied by itself, the result is that expression
[tex] \frac{6 \sqrt{3} }{3} [/tex]
Reduce the fraction with 3
[tex] 2 \sqrt{3} [/tex]
Hope this helps...
Best regards!!
In ΔPQR, the measure of ∠R=90°, RP = 61 feet, and PQ = 89 feet. Find the measure of ∠P to the nearest degree.
Answer:
47°
Step-by-step explanation:
The mnemonic SOH CAH TOA reminds you of the relation ...
Cos = Adjacent/Hypotenuse
The side adjacent to ∠P is the one with P in its name: RP. The hypotenuse is the side opposite the right angle, the side without the right-angle vertex in its name: PQ. So, ...
cos(∠P) = RP/PQ = 61/89
∠P = arccos(61/89) ≈ 46.733°
∠P ≈ 47°
Answer:
47 degrees
Step-by-step explanation:
The Crafty Clay Art Show has invited Aaliyah to make and sell her famous decorative plates. She molds the plates out of clay and then paints them. There is a proportional relationship between the number of plates Aaliyah makes, x, and the amount of clay she uses (in pounds), y. To make 2 plates, Aaliyah uses 6 pounds of clay. Write the equation for the relationship between x and y. (In the form of y= mx)
Answer:
y=3x
Step-by-step explanation:
Number of plates Aaliyah makes=x
Amount of clay she uses (in pounds)= y.
There is a proportional relationship between x and y: y=mx
To make 2 plates, Aaliyah uses 6 pounds of clay.
Therefore:
x=2y=6Substituting the given values into the proportional relationship y=mx, we obtain:
6=2m
Divide both sides by 2
m=3
Therefore, the equation for the relationship between x and y is:
y=3x, where 3 is our constant of proportionality.
5 times the cube of x divided by 4 times x
Answer:
5x^2/4
Step-by-step explanation:
5 times the cube of x divided by 4 times x
(5x^3)/4x=5x^2/4
Answer:
I'm not sure what the question is... but I'm guessing you have to put this in number form? If so, the answer would be 5x^3/4x
Step-by-step explanation:
When having a number times x instead of writing the multiplication sign you just put them next to each other. (5x)
When something is cubed that means it is to the power of three (5x^3)
Divided by four times x would be 4x
Hopefully I did this right and helped you!
11
?
Find the arc length of the semicircle.
Either enter an exact answer in terms of a or
use 3.14 fora and enter your answer as a
decimal.
units
Answer:
[tex]34.5575191895[/tex]
Step-by-step explanation:
[tex]2\pi r(180/360)\\2\pi *11*1/2\\=11\pi[/tex]
The arc length of the semicircle is half the circumference i.e., 11π.
What is circumference?The circumference is the perimeter of a circle.
Formula of Circumference = 2πr.
= Arc length of a semicircle
= half of the circle's circumference
= 2πr/2
= πr
=11r
Learn more about circumference here
https://brainly.com/question/4268218
#SPJ2
Joe walked is dog 3/3 mile every morning how much mike did he walked his dog every morning
Answer:
1 mile.
Step-by-step explanation:
3/3 mile is equal to 1 mile.
Answer:
Joe walked his dog 1 mile.
Step-by-step explanation:
3/3 =1 mile.
RS = 4x — 6 and ST
3x +4. Find RT
maybe hai not sure❤️
Write an equation for line M please and thank you!!!
Answer:
y = -2x + 4
Step-by-step explanation:
First, find the slope by doing rise over run. I did this between the points (0, 4) and (2,0) This gives you -4/2 = -2.
Then, find the y-intercept, which is where the line goes through the y axis. This is at y = 4.
So, the equation is y = -2x + 4.
Answer:
y = -2x + 4
Step-by-step explanation:
Lets write the equation of the line in slope-intercept form. We need to find two things:
1) the y-intercept. When can find this by simply finding what y is equal to when x is 0. Taking a quick look, we can find that it is 4
2) the slope. To find the slope, we simply take the rate of change, or rise over run. Taking the section where x is between 0 and 2, we have, 4/2 = 2.
However, the line is moving downwards, so its a negative slope. This means the actual slope is -2.
Finally, slope-intercept form tells us that the line is y = mx + b, where m is the slope, and b is the y-intercept.
Therefore, the answer is:
y = -2x + 4
The complete factorization of -12x^3 + 14x^2 +6x is -2x(ax + 1)(2x-3). What is the value of a?
Answer:
a = 3
Step-by-step explanation:
-12x³+14x²+6x = -2x(ax+1)(2x-3)
Divide both sides by -2x(2x-3)
[tex]\frac{-2x(ax+1)(2x-3)}{-2x(2x-3)} = - \frac{12x^{3} }{-2x(2x-3)} + \frac{14x^{2} }{-2x(2x-3)} +\frac{6x}{-2x(2x-3)}[/tex]
ax+1=3x+1
Subtract 1 from both sides
ax=3x
Divide both sides by x
a=3
Write and equation that represents the line
Answer:
y = [tex]\frac{3}{4}x+2[/tex]
Step-by-step explanation:
In the figure attached,
Graph of the line passes through the two points (0, 2) and (4, 5).
Let the equation of this line is y = mx + b
Here m = slope of the line
b = y-intercept
Since slope of the line passing through two points is represented by,
m = [tex]\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
= [tex]\frac{(5-2)}{(4-0)}[/tex]
= [tex]\frac{3}{4}[/tex]
Y-intercept of the line 'b' = 2 units
Therefore, equation of the line will be,
y = [tex]\frac{3}{4}x+2[/tex]
Which line is steeper, line a or line b? Justify your reasoning.
Answer:
A
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
Please answer correctly! Will mark brainliest !!!!!!!!!!!!
Answer:
[tex]g^{-1}[/tex](x) = [tex]\frac{x+10}{5}[/tex]
Step-by-step explanation:
Given
g(x) = 5(x - 2)
let y = g(x) and rearrange making x the subject, that is
y = 5(x - 2) ← distribute
y = 5x - 10 ( add 10 to both sides )
y + 10 = 5x ( divide both sides by 5 )
[tex]\frac{y+10}{5}[/tex] = x
Change y back into terms of x with x = [tex]g^{-1}[/tex] (x) , thus
[tex]g^{-1}[/tex](x) = [tex]\frac{x+10}{5}[/tex]